EVALUASI KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK RAWAT JALAN RSUP DR. WAHIDIN SUDIROHUSODO KOTA MAKASSAR - Khaerani, Khaerani; Handayany, Gemy Nastity; Sukamto, Herlinda (Jurnal Kesehatan, 2020)
Patient satisfaction is an indicator of service quality, including in pharmaceutical services. This research about Evaluation of Patient Satisfaction (physical evidence, reliability, responsiveness, empathy, and guarantee) of Pharmaceutical Services at Dr. Wahidin Sudirohusodo’s Pharmacy Makassar period May-July 2017. The purpose of this study was to determine patient satisfaction with pharmacy services at the outpatient pharmacy Dr. Wahidin Sudirohusodo Makassar and To find out how the pharmaceutical service system is implemented by Pharmacists or pharmacist assistants at the Pharmacy. This research is a non-experimental descriptive research and is processed in quantitative analytic using Surveys approach. The population is all outpatients in RSUP Dr. Wahidin Sudirohusodo for the period May-July 2017 and 100 subjects were obtained. Primary data were obtained through research instruments using a questionnaire, then analyzed by univariate and bivariate analysis. The results showed that based on statistical analysis, 57% of respondents said they were satisfied with the service and the rest were less satisfied. Pharmacy Service System implemented by Pharmacists and Pharmacist Assistants is already good and carrying out their duties according to applicable SOPs only needs to be improved because the analysis results use the Chi square formula x2 count ≥ x2 tables then H0 is rejected meaning there is a significant difference between variable reliability, responsiveness, assurance, empathy and physical evidence.